2015
DOI: 10.1016/j.jhealeco.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Staffing subsidies and the quality of care in nursing homes

Abstract: Concerns about the quality of state-financed nursing home care has led to the wide-scale adoption by states of pass-through subsidies, in which Medicaid reimbursement rates are directly tied to staffing expenditure. We examine the effects of Medicaid pass-through on nursing home staffing and quality of care by adapting a two-step FGLS method that addresses clustering and state-level temporal autocorrelation. We find that pass-through subsidies increases staffing by about 1% on average and 2.7% in nursing homes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Their results are consistent with a model in which regulated wages act like a price ceiling in certain markets that makes it difficult for hospitals to recruit and retain nurses, especially those of high quality. Also in line with the idea that more pay for nurses generates higher quality nursing services, Foster and Lee (2015) show that Medicaid pass-through subsidies-which provide additional funds earmarked for higher pay or more employment of staff--were associated with both increased staffing and decreased pressure ulcers among nursing home residents. Looking more directly at the impacts of nursing staff, Gruber and Kleiner (2012) find that nurse strikes substantially increase within-hospital mortality rates for patients admitted during a strike, despite largely unchanged patient characteristics or treatment intensities.…”
Section: Introductionsupporting
confidence: 52%
“…Their results are consistent with a model in which regulated wages act like a price ceiling in certain markets that makes it difficult for hospitals to recruit and retain nurses, especially those of high quality. Also in line with the idea that more pay for nurses generates higher quality nursing services, Foster and Lee (2015) show that Medicaid pass-through subsidies-which provide additional funds earmarked for higher pay or more employment of staff--were associated with both increased staffing and decreased pressure ulcers among nursing home residents. Looking more directly at the impacts of nursing staff, Gruber and Kleiner (2012) find that nurse strikes substantially increase within-hospital mortality rates for patients admitted during a strike, despite largely unchanged patient characteristics or treatment intensities.…”
Section: Introductionsupporting
confidence: 52%
“…Thus, ongoing personnel management by hospitals should contribute to improving healthcare quality. Providing employees with incentives for positive outcomes (e.g., decreases in pressure ulcers) and making efforts to increase their satisfaction and decrease turnover rates should be considered by LTCH managers who wish to improve healthcare quality [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Policy-makers could compel nursing homes to spend a certain amount of the Medicare and Medicaid revenues on staff through the adoption of wage pass-through requirement or wage floors. Some states already employ such measures, and research has found them to modestly improve residents' outcomes (Foster and Lee 2015). To the extent that such measures also result in better benefits for direct care workers, including paid sick days and better health benefits, such reforms could make nursing homes better prepared to respond to infectious disease outbreaks by allowing staff to stay home when sick and access needed health services.…”
Section: Higher Wages For Direct Care Staffmentioning
confidence: 99%